SERPINE2 Overexpression Is Associated with Poor Prognosis of Urothelial Carcinoma - Hao-Wen Chuang; Kan-Tai Hsia; Jia-Bin Liao; Chih-Ching Yeh; Wei-Ting Kuo; Yi-Fang Yang (Diagnostics, 2021)
Recent studies have reported that SERPINE2 contributes to the development of various cancers. However, its association with urothelial carcinoma (UC) remains unclear. In this study, data on urinary bladder UC (UBUC) cases from The Cancer Genome Atlas (TCGA) database were used to investigate the prognostic value of SERPINE2 mRNA expression. Then, SERPINE2 expression was analyzed with tissue microarrays constructed from 117 upper tract UC (UTUC) and 84 UBUC tissue specimens using immunohistochemical staining. Results were compared to clinicopathologic data by multivariate analysis. In the TCGA database, high SERPINE2 mRNA expression indicated a poor prognosis in patients with UBUC. Furthermore, Mann–Whitney U test showed that high SERPINE2 immunoexpression was significantly associated with adverse pathologic parameters including invasion, high grade, coexistence of UC in situ, and advanced pT stage (all p < 0.05, except for a marginal association with high-grade UBUC, p = 0.066). Kaplan–Meier analysis revealed that high SERPINE2 expression was associated with worse overall survival (OS; UTUC, p = 0.003; UBUC, p = 0.014) and disease-free survival (UTUC, p = 0.031; UBUC, p = 0.033). Moreover, multivariate analysis identified high SERPINE2 expression as an independent prognostic factor for OS (UTUC, p = 0.002; UBUC, p = 0.024). Taken together, our findings demonstrated that increased SERPINE2 expression is associated with adverse pathologic features and may serve as a prognostic biomarker for UC.